Health Tecnology Assessment and Health Policy Today: A Multifacered View of Their Unstable Crossroads - Del Llano-Senaris, Juam E. (Springer, 2015)
Health Tecnology Assessment and Health Policy Today: A Multifacered View of Their Unstable Crossroads